Reeder and Felson’s Gamuts in Bone, Joint and Spine Radiology Comprehensive Lists of Roentgen Differential Diagnosis - Reeder, Maurice M. (Springer New York, 1993)
All the gamuts pertaining to orthopaedics and rheumatology have been excerpted from Reeder and Felson's Gamuts in Radiology, the world's best known, most trusted, and most comprehensive guide to radiologic differential diagnosis. The gamuts have been reorganized and renumbered for ease of use. This book is especially useful for residents in orthopaedics and rheumatology. Features of this spinoff include: - a slim 4 x 8" trim size for ease of carrying; - an easy to read single-column format; - a concentrated listing of orthopaedic gamuts